Synthesis of Silver Nitrate by Evaporation Chemical Reduction Process as Potential Materials for Silver Nanowires Application - Junaidi; Malik, Daffa Abdul; Rizki, Muhammad; Pratiwi, Indah; Karo-Karo, Pulung; Marjunus, Roniyus; Asmi, Dwi; Hadi, Sutopo (Science and Technology Indonesia, 2024)
In this study, we conducted the extraction of silver nitrate (AgNO3) using the chemical reduction evaporation method, involving silver metal (Ag) with a molarity of 7.716 M and nitric acid (HNO3). The heating process via evaporation was carried out at 85oC for 2 hours. Subsequently, the synthesis of silver nanowires (AgNWs) was performed using a 0.3 M of AgNO3 solution in ethylene glycol (EG), polyvinyl pyrrolidone (PVP), and Iron (III) Chloride hexahydrate (FeCl36H2O). XRD analysis of the AgNO3 sample revealed an orthorhombic crystal structure with a single AgNO3 phase peak. In AgNWs, three crystalline phases were observed, with the Ag phase being the most dominant. The average crystal size of AgNO3 and AgNWs was 109.42 nm and 22.06 nm, respectively. The average crystal size of the AgNO3 sample may be influenced by the aggregation between crystal nuclei during the heating process. XRF analysis indicated a 98.84% Ag concentration in AgNO3. SEM-EDS analysis showed that the AgNO3 sample had a non-aggregated morphological structure, with particle size measuring 49.46 μm and an overall AgNO3 purity of 92.68%. The SEM image of the AgNWs sample displayed a very homogeneous diameter of ∼200 nm with a length of around 10-20 μm. Meanwhile, AgNWs exhibited a morphology resembling rod-shaped wires with a purity of 68% for Ag.